Development of an indirect ELISA for detection of antibody to wobbly possum disease virus in archival sera of Australian brushtail possums (Trichosurus vulpecula) in New Zealand. Issue 4 (4th July 2018) - Giles, JC; Johnson, W; Jones, G; Heuer, C; Dunowska, M
Abstract: AIMS: To develop an indirect ELISA based on recombinant nucleocapsid (rN) protein of wobbly possum disease (WPD) virus for investigation of the presence of WPD virus in Australian brushtail possums ( Trichosurus vulpecula ) in New Zealand. METHODS: Pre- and post-infection sera (n=15 and 16, respectively) obtained from a previous experimental challenge study were used for ELISA development. Sera were characterised as positive or negative for antibody to WPD virus based on western-blot using WPD virus rN protein as antigen. An additional 215 archival serum samples, collected between 2000–2016 from five different regions of New Zealand, were also tested using the ELISA. Bayesian modelling of corrected optical density at 450 nm (OD450 ) results from the ELISA was used to obtain estimates of receiver operating characteristic (ROC) curves to establish cut-off values for the ELISA, and to estimate the prevalence of antibody to WPD virus. RESULTS: Western blot analysis showed 5/14 (36%) pre-infection sera and 11/11 (100%) post-infection sera from experimentally infected possums were positive for antibodies to WPD virus. Bayesian estimates of the ROC curves established cut-off values of OD450 ≥0.41 for samples positive, and OD450 <0.28 for samples negative for antibody to WPD virus, for sera diluted 1:100 for the ELISA. Based on the model, the estimated proportion of samples with antibodies to WPD virus was 0.30 (95% probability interval=0.196–0.418). Of the 230 archival serum samples tested using the ELISA, 48 (20.9%) were positive for antibody to WPD virus, 155 (67.4%) were negative and 27 (11.7%) equivocal, using the established cut-off values. The proportion of samples positive for WPD virus antibody differed between geographical regions (p<0.001). CONCLUSION: The results suggested that WPD virus or a related virus has circulated among possums in New Zealand with differences in the proportion of antibody-positive samples from different geographical regions. Antibodies to WPD virus did not seem to protect possums from disease following experimental infection, as one third of possums from the previous challenge study showed evidence of pre-existing antibody at the time of challenge. These results provide further support for existence of different pathotypes of WPD virus, but the exact determinants of protection against WPD and epidemiology of infection in various regions of New Zealand remain to be established. CLINICAL RELEVANCE: Availability of the indirect ELISA for detection of WPD virus antibody will facilitate prospective epidemiological investigation of WPD virus circulation in wild possum populations in New Zealand.